(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Livedoid vasculopathy is a chronic skin condition associated with coagulation disorders, leading to thromboembolism in the dermal blood vessels and necrotizing ulceration of the skin. The management of livedoid vasculopathy remains challenging, as it is often misdiagnosed as cutaneous vasculitis and shows poor response to corticosteroids. Case series: Ten patients with livedoid vasculopathy presenting with recurrent painful ulceration on both legs were treated with oral rivaroxaban. All patients showed favourable responses, complete ulcer healing, and rapid pain relief. Adverse effects included menorrhagia in two patients. Discussion: New insights into the pathogenesis have shifted treatment perspectives towards prioritizing anticoagulant therapy over an approach similar to vasculitis. Menorrhagia was reported in two cases, while no major bleeding events according to ISTH criteria were observed. Our preliminary findings suggest that rivaroxaban has favorable clinical efficacy and an acceptable safety profile in the treatment of thrombotic livedoid vasculopathy. Conclusion: The results from this case series provide additional evidence supporting the effectiveness of rivaroxaban in the treatment of livedoid vasculopathy, providing physicians with additional data to develop more optimal treatment strategies for patients.